Hemodialysis technology - Ronco, Claudio 1951-; La Greca, Giuseppe (Contributions to nephrology, 2002)
This publication is a collection of the papers presented at the 'First International Course on Hemodialysis Technology', Vicenza, June 2002: It covers a wide range of topics, including aspects of vascular access and new forms of monitoring access function. Moreover, anticoagulation strategies and antimicrobial treatment are debated, with special emphasis on temporary catheters and prosthetic devices.Membrane composition and structure, their methods of sterilization and performance are discussed by experts and manufacturers, bringing together in a unique way science, theory and manufacturing procedures. The same synthesis is achieved with respect to hemodialyzers, adsorbent devices, dialysis techniques and machines. A new issue is the possibility of computer-assisted data collection and management: This subject is discussed by experts in electronic data management, together with managers of large dialysis networks, concentrating on matters of quality assurance and continuous quality improvement programs.Special attention is given to dialysate and water purity since this is the starting point for newer dialytic techniques such as online hemodiafiltration. Moreover, the results obtained from the IDOPPS study are incorporated into the discussion of different practice patterns and anemia management. Finally, future trends are explored including automatic sensors and biofeedback monitors.Covering various aspects of hemodialysis technology, this book will be a helpful tool for physicians and nurses, both for education and information